Mechanism-based inactivation of cytochrome p450 2A6 by decursinol angelate isolated from Angelica gigas - Yoo, Hye Hyun; Lee, Min Woo; Kim, Young Choong; Yun, Chul-Ho; Kim, Dong-Hyun (AMER SOC PHARMACOLOGY EXPERIMENTAL THERAPEUTICS, 2007)
The inhibition of CYP2A6 by decursinol angelate, a pyranocoumarin isolated from Angelica gigas roots, was examined in human liver microsomes and recombinant CYP2A6. Decursinol angelate moderately inhibited coumarin 7-hydroxylation, but a 20-min pre-incubation with microsomes and NADPH significantly increased its inhibitory effect (IC50; > 20 versus 4.4 mu M). A similar inhibition pattern was observed in nicotine C oxidation, which is also one of the prototype reactions of CYP2A6. Inactivation by decursinol angelate was selective for CYP2A6 and characterized by K-1 values of 0.99 and 2.42 mu M and the k(inact) values of 0.136 and 0.053 min(-1) in microsomes and recombinant CYP2A6, respectively. This inactivation was not protected or restored by nucleophiles, reactive oxygen scavengers, or extensive dialysis but was inhibited by the addition of a competitive CYP2A6 inhibitor, pilocarpine. Furthermore, incubation of CYP2A6 with decursinol angelate in the presence of NADPH resulted in a loss of the spectral CYP2A6 content. An in vitro metabolism study revealed that CYP2A6 oxidized decursinol angelate to the dihydrodiol metabolite, presumably via an epoxide intermediate that might be responsible for the inactivation of CYP2A6. These results collectively demonstrated that decursinol angelate inactivated CYP2A6 in a mechanism-based mode.
Keywords: GENETIC-POLYMORPHISM; CYP2A6 GENE; NICOTINE; PURIFICATION; INHIBITORS; EXPRESSION; COUMARINS; RISK